2005
DOI: 10.1592/phco.2005.25.10.1310
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Intravenously Administered Levofloxacin in Men and Women

Abstract: Differences exist in the disposition of levofloxacin between healthy men and women after systemic administration. Fixed intravenous doses of levofloxacin will lead to greater drug exposure in women. Thus, women may have more of an increased risk of fluoroquinolone toxicity than men, and men may need higher doses to achieve similar drug efficacy than women. Levofloxacin dosage adjustments based on sex should be considered on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
6
0
2
Order By: Relevance
“…Overholser et al compared the pharmacokinetics of intravenous LVX after a single 500 mg dose in men and women who showed no significant difference in body mass index, and observed that women had a 24% greater exposure (AUC) to LVX, with a significantly smaller V ss ( P <0.01) and a slower clearance ( P <0.01) 17. When pharmacokinetic parameters were adjusted for both lean and total body weight, the difference in clearance was attenuated, but V ss remained significantly smaller in women than in men, indicating a sex difference in V ss after intravenous administration of LVX.…”
Section: Resultsmentioning
confidence: 99%
“…Overholser et al compared the pharmacokinetics of intravenous LVX after a single 500 mg dose in men and women who showed no significant difference in body mass index, and observed that women had a 24% greater exposure (AUC) to LVX, with a significantly smaller V ss ( P <0.01) and a slower clearance ( P <0.01) 17. When pharmacokinetic parameters were adjusted for both lean and total body weight, the difference in clearance was attenuated, but V ss remained significantly smaller in women than in men, indicating a sex difference in V ss after intravenous administration of LVX.…”
Section: Resultsmentioning
confidence: 99%
“…For some analgesics, anxiolytics and hypnotics, including certain benzodiazepines, drug plasma concentrations tend to be higher in women than in men. [14][15][16][17] Furthermore, drugs metabolised by hepatic oxidation have a prolonged elimination half-life in women taking contraceptives. [14] Some physiological differences related to gender may also influence drug metabolism, including muscle mass, hormonal status, disposition of the adipose tissue, gastric secretion and motility, and other physiological conditions such as the menstrual cycle and pregnancy.…”
Section: Pharmacological and Pharmacogenetic Differences Related To Gmentioning
confidence: 99%
“…Aufgrund der generell niedrigeren Körpermasse bei Frauen muss eine höhere Konzentration angenommen werden, wenn die Dosierung nicht adäquat an das Körpergewicht angepasst wird [12]. So wurden höhere Arzneimittelkonzentrationen bei Frauen häufi-ger gefunden [13]. Unter der Berücksichti-gung, dass eine eingeschränkte renale wie hepatische Funktion im Alter zu höheren Blut-und Plasmaspiegeln führt, war die Fläche unter den Konzentrations-ZeitKurven von Arzneistoffen bei geriatrischen Patienten weiterhin im Mittel erhöht [14].…”
unclassified
“…Demgegenüber lässt die Untersuchung aber auch den Schluss zu, dass QTc-Intervall-verlän-gernde Arzneistoffe von Frauen <60 Jahre noch relativ gut vertragen werden. Zumindest wurde bei der vorgegebenen Patientenzahl im Vergleich zu kritisch kranken Männern kein erhöhtes Risiko festgestellt (6/22 Frauen vs. 8/27 Männer).Unter der Berücksichtigung, dass eine eingeschränkte renale und hepatische Funktion im Alter sowie im kritischen Zustand zu höheren Blut-und Plasmaspiegeln führen dürfte, stehen die ermittelten Ergebnisse im Einklang mit der Annahme, dass v. a. bei Frauen mit niedrigerem Körpergewicht die üblichen Dosierungen, d. h. ohne Anpassung an das niedrige Körpergewicht, zu hohen Konzentrationen in Blut und Gewebe führen[12,13]. Dies sollte insbesondere dann klinisch bedeutsam werden, wenn sie schwer erkrankt sind und demzufolge nur noch wenige Kompensationsreserven besitzen.Als Indiz dafür, dass bei Frauen eine relative Überdosierung zumindest mitverantwortlich ist, spricht auch die Feststellung, dass schon die unter Therapie auswertbaren QTc-Intervalle (73%) bei Frauen zwischen Überleben und Versterben zu unterscheiden vermochten (p=0,014), insbesondere hinsichtlich der Entwicklung seit Aufnahme (p=0,001).…”
unclassified